2013
DOI: 10.1007/s11069-013-0696-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a major storm over the Dongjiang reservoir basin associated with Typhoon Bilis (2006)

Abstract: An unexpected major storm on July 14, 2006, resulted in great loss to the Dongjiang reservoir basin in Zixing City, Hunan Province, China, during the dominance of Typhoon Bilis (2006). The rainfall characteristics and temporal evolution of this major storm were studied with rain gauge data and high-resolution radar reflectivity data to investigate the connections between typhoon, reservoir and convective storm. Our investigations found that the intense convective storm, which was characterized by a banded stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…This is especially valid in arid and Mediterranean climates (Degu et al 2011;Zhao et al 2012;Hossain 2010;Hossain et al 2010), as for such conditions, the triggering potential might be considered medium or strong. The weak interrelation to climate also encompasses the special case reported on a large reservoir, where Zou et al (2013) found an increasing risk of convective storms. Another example of weak interrelation is the remote possibility of a hazard chain initiated by an RTE that might further trigger events leading to glacial outburst floods.…”
Section: Importance Of the Interrelations For Reservoirs And Damsmentioning
confidence: 88%
“…This is especially valid in arid and Mediterranean climates (Degu et al 2011;Zhao et al 2012;Hossain 2010;Hossain et al 2010), as for such conditions, the triggering potential might be considered medium or strong. The weak interrelation to climate also encompasses the special case reported on a large reservoir, where Zou et al (2013) found an increasing risk of convective storms. Another example of weak interrelation is the remote possibility of a hazard chain initiated by an RTE that might further trigger events leading to glacial outburst floods.…”
Section: Importance Of the Interrelations For Reservoirs And Damsmentioning
confidence: 88%